Nad slovenskými prekladmi Wisławy Szymborskej - Obertová, Zuzana (Przekłady Literatur Słowiańskich, 2017)
On Slovak Translations of Wisława Szymborska’s Poems This paper deals with the Slovak translations of poems by Wisława Szymborska who was awarded Nobel Prize in 1996. Twenty years later two collection of her poems were published in the Slovak language. The author of this paper summarized all translations of W. Szymborska’s poems into the Slovak language which have been published in literature magazines as well as books since 1952, the year of the poet’s debut. Since some poems were translated more than once by different translators, the phenomenon of retranslation is also discussed. Various translations of three poems are compared and analyzed in the paper as well. Keywords: Wisława Szymborska, literary translation, retranslation, interpretation, poem